การพัฒนารูปแบบการประเมินผลการเรียนรู้ตามสภาพจริง : กรณีศึกษา คณะศึกษาศาสตร์ สาขาวิชาการสอนภาษาไทย วิทยาลัยศาสนศาสตร์ยโสธร - พันผาด, วรัญรัตน์; (มุลชิวะ), พระมหาจิรายุทธ ปโยโค; จินดารัมย์, ณัฐพล (วารสาร มมร ยศสุนทรปริทรรศน์, 2024)
The objective of this research was to study the knowledge and models of authentic assessment, to evaluate the efficiency and effectiveness of authentic assessment, and to apply the evaluation results to teaching and learning management at the College of Religious Studies in Yasothon University. The study involved 123 participants. The research tool used was an authentic assessment form, and the statistics applied were parameters, standard deviation, and efficiency and effectiveness based on the 80/80 criterion. The research results showed that student satisfaction with authentic assessment was at a moderate level (µ = 3.12, S.D. = 0.77). The efficiency of the assessment system after improvement was 81.22/83.04, and the development of the authentic assessment model demonstrated significant effectiveness at the .05 level.